1991
DOI: 10.1104/pp.96.2.558
|View full text |Cite
|
Sign up to set email alerts
|

Hydrotropism and Its Interaction with Gravitropism in Maize Roots

Abstract: We have partially characterized root hydrotropism and its interaction with gravitropism in maize (Zea mays L.). Roots of Golden Cross Bantam 70, which require light for orthogravitropism, showed positive hydrotropism; bending upward when placed horizontally below a hydrostimulant (moist cheesecloth) in 85% relative humidity (RH) and in total darkness. However, the lightexposed roots of Golden Cross Bantam 70 or roots of a normal maize cultivar, Burpee Snow Cross, showed positive gravitropism under the same con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 13 publications
3
46
0
Order By: Relevance
“…ABA also substituted partially for the light effect and enhanced the Ca2+-stimulated curvature of Alaska pea roots in the dark (Table V) Elevation of cytoplasmic Ca2" levels in the root cap, previously proposed to play an important role in signal transduction of gravity (2,19,23,25), could participate in gravitropic curvature of roots through its stimulatory action because many studies have shown that an acceleration of root elongation takes place following gravistimulation (13,14,26). In this regard, root curvature away from a Ca2" source appears to be the opposite of reports that there is a Ca2' redistribution with more accumulation on the bottom side of the graviresponding roots curving down (18,21 Differences in responsiveness of roots to Ca2" may also result from different water conditions at the tip as described in "Materials and Methods" (20,29). However, it is now evident that roots of many cultivars of corn and pea, including all those tested in the present study, curve away from Ca2+ when applied unilaterally to the root cap and that the response is concentration dependent (Fig.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…ABA also substituted partially for the light effect and enhanced the Ca2+-stimulated curvature of Alaska pea roots in the dark (Table V) Elevation of cytoplasmic Ca2" levels in the root cap, previously proposed to play an important role in signal transduction of gravity (2,19,23,25), could participate in gravitropic curvature of roots through its stimulatory action because many studies have shown that an acceleration of root elongation takes place following gravistimulation (13,14,26). In this regard, root curvature away from a Ca2" source appears to be the opposite of reports that there is a Ca2' redistribution with more accumulation on the bottom side of the graviresponding roots curving down (18,21 Differences in responsiveness of roots to Ca2" may also result from different water conditions at the tip as described in "Materials and Methods" (20,29). However, it is now evident that roots of many cultivars of corn and pea, including all those tested in the present study, curve away from Ca2+ when applied unilaterally to the root cap and that the response is concentration dependent (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…(16,19). Accordingly, excess water or swollen mucilage on the root surface, of particular importance in corn (20,29), was carefully removed with filter paper before treatment with agar blocks, while using care to avoid drying during experimental manipulations.…”
mentioning
confidence: 99%
“…A database search performed by using the BLAST algorithm revealed that a homolog of MIZ1 is encoded in the rice genome (26), suggesting that MIZ1 functions in hydrotropism in both dicotyledonous and monocotyledonous plants. Indeed, hydrotropism also has been reported in monocotyledonous plants (27,28). MIZ1 contains a previously uncharacterized domain (DUF617) whose function has not yet been defined even though the domain is present in various plant proteins from diverse species (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…However, little attention © 1997 Blackwell Science Ltd has been paid to hydrotropism because it is so difficult to separate from geotropism. Recently, it was demonstrated clearly in an ageotropic pea mutant (Jaffe et al 1985;Takahashi & Suge 1991) and then in Alaska pea (Takahashi & Suge 1991), maize (Takahashi & Scott 1991) and wheat (Oyanagi et al 1995) that roots exhibit positive hydrotropism in an apparatus in which the gradient in air humidity can be precisely controlled. Moreover, the extent of root hydrotropic curvature increased with increases in the humidity gradient in the apparatus (Takahashi & Scott 1993;Oyanagi et al 1995).…”
Section: Introductionmentioning
confidence: 99%